2015
DOI: 10.5173/ceju.2015.543
|View full text |Cite
|
Sign up to set email alerts
|

An up-to-date overview of minimally invasive treatment methods in ureteropelvic junction obstruction

Abstract: IntroductionOver the last two decades, minimally invasive treatment options for ureteropelvic junction obstruction have been developed and are bcoming more popular. Multiple series of laparoscopic pyeloplasty have demonstrated high success rates and low perioperative morbidity in pediatric and adult populations, for both the transperitoneal and retroperitoneal approaches. In this review, we aimed to analyze the current status of minimally invasive therapy of ureteropelvic junction obstruction.Material and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 70 publications
0
13
0
1
Order By: Relevance
“…Open pyeloplasty is still considered to be the gold standard in all age groups as it can be done [8]. On contrary, MIS requires more expertise and comparatively long learning curve (laparoscopy has even longer learning curve than robotic) [9].…”
Section: Discussionmentioning
confidence: 99%
“…Open pyeloplasty is still considered to be the gold standard in all age groups as it can be done [8]. On contrary, MIS requires more expertise and comparatively long learning curve (laparoscopy has even longer learning curve than robotic) [9].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, pyeloplasty is the method of choice to treat patients with UPJO applied by Treudelem in 1886 for the first time. Although, different methods are proposed to treat UPJO, dismembered pyeloplasty remains the most popular surgical technique for years (4). Surgical pyeloplasty technique is improved during recent decades especially in the era of minimally invasive approach.…”
Section: Introductionmentioning
confidence: 99%
“…RAPY has been proposed to have an advantage over LPY by having a shorter learning curve and suturing time; however, at present there are no well-designed RCTs comparing effectiveness between LPY and RAPY [63] . Several comparative series have suggested that RAPY benefits from having a shorter operative time when compared with LPY, but no other differences were found [59] , [63] , [64] , [65] . A population-based study using the USA Perspective Database found that the median cost of RAPY was significantly higher than OPY, whilst there was no statistical difference between the median cost of OPY and LPY [50] .…”
Section: Resultsmentioning
confidence: 99%